1994
DOI: 10.1007/bf01973986
|View full text |Cite
|
Sign up to set email alerts
|

Reporter genes in transgenic mice

Abstract: Although in vivo models utilizing endogenous reporter genes have been exploited for many years, the use of reporter transgenes to dissect biological issues in transgenic animals has been a relatively recent development. These transgenes are often, but not always, of prokaryotic origin and encode products not normally associated with eukaryotic cells and tissues. Some encode enzymes whose activities are detected in cell and tissue homogenates, whereas others encode products that can be detected in situ at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(35 citation statements)
references
References 145 publications
(118 reference statements)
1
34
0
Order By: Relevance
“…An equivalent discrepancy has been noted with a lacZ knock-in at the bim locus, which also presents very low or undetectable ␤-galactosidase activity in lymphoid areas of the lymph node, thymus, and spleen, even though RNA and protein analyses clearly indicate Bim expression in these cells (P. Bouillet, unpublished observation) (32), in which loss of Bim profoundly impairs apoptosis (4,5). Silencing of lacZ transgenes in hematopoietic cells has been documented previously (12,31), and hence silencing of the reporter gene might contribute to the lack of ␤-galactosidase activity in the lymphocytes in which it is located in the bik or bim locus. Another possibility is that a regulatory element needed for lymphoid expression of the locus resides within the region deleted in the replacement, such as in the deleted intron.…”
Section: Discussionsupporting
confidence: 52%
“…An equivalent discrepancy has been noted with a lacZ knock-in at the bim locus, which also presents very low or undetectable ␤-galactosidase activity in lymphoid areas of the lymph node, thymus, and spleen, even though RNA and protein analyses clearly indicate Bim expression in these cells (P. Bouillet, unpublished observation) (32), in which loss of Bim profoundly impairs apoptosis (4,5). Silencing of lacZ transgenes in hematopoietic cells has been documented previously (12,31), and hence silencing of the reporter gene might contribute to the lack of ␤-galactosidase activity in the lymphocytes in which it is located in the bik or bim locus. Another possibility is that a regulatory element needed for lymphoid expression of the locus resides within the region deleted in the replacement, such as in the deleted intron.…”
Section: Discussionsupporting
confidence: 52%
“…A replication defective recombinant adenoviral vector expressing the E. coli ␤-galactosidase transgene, the most commonly used in situ reporter in preclinical development of gene transfer protocols (Cui et al, 1994) and routinely used in our laboratory, was administered in these studies. One day after administration of either 5.7 ϫ 10 11 or 5.7 ϫ 10 12 vp/kg of this vector, CYP3A1/2 protein expression was significantly suppressed by 59 and 60%, respectively, compared with the vehicle treatment group (P Յ 0.01, Fig.…”
Section: Effect Of Administration Of High Doses Of Adlacz Onmentioning
confidence: 99%
“…This conclusion may seem surprising, because lacZ has been widely used, particularly in studies on embryogenesis. However, a review on lacZ as a transgenic reporter (Cui et al, 1994) concluded that`its postnatal in vivo expression has been unreliable and disappointing'. Its erratic performance in long-term experiments would be explicable if the bacterial sequences stochastically inactivated certain linked promoters, so that the proportion of non-expressing cells increased over time.…”
Section: Variegation Of Expression Induced By the Reportermentioning
confidence: 99%